System Identification of Railway Trains Pantograph for Active Pantograph Simulation - ABDULLAH, Mohd Azman; MICHITSUJI, Yohei; NAGAI, Masao; VENTURE, Gentiane (The Japan Society of Mechanical Engineers, 2011)
High performance of the contact wire and pantograph dynamic interaction is required in the operation of high speed railway vehicles. Due to the constraint of field test, simulation and lab experiment procedures are performable to verify the interaction. Such simulation needs accurate modeling of the response of the pantograph for the consistency in prediction and control. A simple system identification of the pantograph is executed based on the lab experimental data using commercial software and least squares method. The validation of the procedure is performed through comparison between extended experimental data and numerical simulations of the pantograph system. Further analysis is by applying active pantograph control on the system by simulation. The results show availability of the design for active pantograph system.